PEMANFAATAN TEPUNG SUKUN (Artocarpus altilis sp.) PADA PEMBUATAN ANEKA KUDAPAN SEBAGAI ALTERNATIF MAKANAN BERGIZI UNTUK PMT-AS - Dewanti Putri Pratiwi; Ahmad Sulaeman; Leily Amalia (Jurnal Gizi dan Pangan, 2012)
Breadfruit is valuable fruit and has a good of nutrient content, but its usage is limited by poor storage properties of fresh fruit. Processing into flour, can increase its utilization. The aim of this research was to utilize breadfruit flour in production of nutritious snack foods for School Supplementary Feeding Programme (PMT-AS). There were three products developed in this study; brownies, pia, and croquette. The research was conducted using experimental design. The proportions of breadfruit flour and wheat flour were different for each product, which brownies was formulated using 70:30, 80:20, 90:10, and 100:0; whereas pia and croquette was formulated by 50:50, 60:40, 70:30, and 80:20. Proximate analysis showed that 100 g brownies contained 409 kcal energy and 7.5 g protein, 100 g pia had 383 kcal energy and 6.7 g protein and croquette had the highest energy and protein content is 455 kcal and 9.9 g protein. In conclusion, all products were suitable as alternative snacks for PMT-AS. The products have met 300 kcal energy and 5 g protein per serving size. Considered also the cost of production, these products have fulfilled criteria to be used in PMT-AS.